Meningkatkan Kualitas Pendidikan di Indonesia: Pengelolaan Sarana dan Prasarana Sekolah Dasar - ketut susiani (UHN IGB Sugriwa Denpasar, 2022)
Facilities and infrastructure (Sarpras) in primary to tertiary education have an important role in the learning process. The role and position of facilities and infrastructure are very important in attracting the attention of the community so that schools have enthusiasts. This paper aims to determine the management system for school infrastructure in improving the quality of education in Indonesia. Methods This research uses comparative journals related to facilities and infrastructure in the field of education. Based on the results of library reviews from various countries in the world, the authors found that (1) to improve the quality of education, supporting and efficient facilities and infrastructure were needed, (2) managing and utilizing the facilities and infrastructure available in schools as a benchmark in improving the quality of education